THE OCCURRENCE OF DIFFERENT STAGES OF SPINY LOBSTERS IN KAKINADA REGION - Devi, S Lalitha (Indian Journal of Fisheries, 2011)
The occurrence of puemulusi, juvenile and aidiult stages of spiny lobsters ofthe genus Panulirus is reported from the 'Bay and estuary of Kakinada region. Theoccurrence of juvenile of P. homarus up to 132 mm length in the Godaivaryestuary and the pueruli of P. polyphagus in this region are new records